Efficacy of heat treatment for disinfestation of concrete grain silos. - Opit, G.P.; Arthur, F.H.; Bonjour, E.L.; Jones, C.L.; Phillips, Thomas W. (My University, 2011)
Field experiments were conducted in 2007 and 2008 to evaluate heat treatment for disinfestations of empty concrete elevator silos. A Mobile Heat Treatment Unit was used to introduce heat into silos to attain target conditions of 50°C for at least 6 h. Ventilated plastic containers with a capacity of 100 g of wheat, Triticum aestivum L., held Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) and Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). Polyvinyl chloride containers with a capacity of 300 g of wheat held adults of Liposcelis corrodens (Heymons) (Psocoptera: Liposcelididae) and Liposcelis decolor (Pearman), which were contained in 35-mm Petri dishes within the grain. Containers were fastened to a rope suspended from the top of the silo at depths of 0 m (just under the top manhole), 10 m, 20 m, and 30 m (silo floor). When the highest temperature achieved was ≍50°C for 6 h, parental mortality of R. dominica and T. castaneum, and both psocid species was 98-100%. Progeny production of R. dominica occurred when there was parental survival, but in general R. dominica seemed less impacted by the heat treatment than T. castaneum. There was 100% mortality of L. corrodens at all depths in the heat treatments but only 92.5% mortality for L. decolor, with most survivors located in the bioassay containers at the top of the silo. Results show wheat kernels may have an insulating effect and heat treatment might be more effective when used in conjunction with sanitation and cleaning procedures.
Citation: Opit, G. P., F. H. Arthur, E. L. Bonjour, C. L. Jones, and T. W. Phillips. 2011. “Efficacy of Heat Treatment for Disinfestation of Concrete Grain Silos.” Journal of Economic Entomology 104 (4): 1415–22. https://doi.org/10.1603/EC11104.
Keywords: Rhyzopertha dominica; Tribolium castaneum; Liposcelis corrodens; Liposcelis decolor; Heat treatment